DNA Computing and Molecular Programming 16th International Conference, DNA 16, Hong Kong, China, June 14-17, 2010, Revised Selected Papers - Sakakibara, Yasubumi; Mi, Yongli; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the thoroughly refereed post-conference proceedings of the 16th International Conference on DNA Computing and Molecular Programming, DNA16, held in Hong Kong, China, in June 2010. The 16 revised full papers presented were carefully selected during two rounds of reviewing and improvement from 59 submissions. The papers are well balanced between theoretical and experimental work and address all areas that relate to biomolecular computing, including demonstrations of biomolecular computing, theoretical models of biomolecular computing, biomolecular algorithms, computational processes in vitro and in vivo, analysis and theoretical models of laboratory techniques, biotechnological and other applications of DNA computing, DNA nanostructures, DNA devices such as DNA motors, DNA error evaluation and correction, in vitro evolution, molecular design, self-assembled systems, nucleic acid chemistry, and simulation tools.
Keywords: Computer science; Data structures (Computer science).; Computers; Algorithms; Artificial intelligence; Bioinformatics; Computer Science; Computation by Abstract Devices; Algorithm Analysis and Problem Complexity; Computational Biology/Bioinformatics.; Artificial Intelligence (incl. Robotics).; Data Structures; Electronic books